Who Was a Bahā’ī in the Upper Echelons of Qājār Iran? - Moojan Momen (Religions, 2023)
This paper addresses two questions: first, that of the nature of multiple religious identities in a traditional society; second, that of who can be identified as Bahā’īs in the upper echelons of Qājār Iran. The paper identifies five criteria by which individuals can be identified as having been Bahā’īs and suggests that, since none of these are usually conclusive by themselves, more than one of the criteria should be fulfilled before we label someone as a Bahā’ī. The various grades of being a Bahā’ī are also examined. The paper lists a number of examples of people from the Qājār royal family and from among the highest echelons of the Qājār administration who fulfill these criteria. It also looks at two individuals who have not been claimed to be Bahā’īs in the usual Iranian and Bahā’ī histories, and yet, if a close study of their lives is made, considerable evidence can be accumulated that they may have been crypto-Bahā’īs. In all, this paper indicates that there may have been many Bahā’īs in the upper strata of Qājār society, that this is a factor that has not previously been sufficiently recognized and needs to be examined for the light that it may shed on other matters.